Numerical Simulation Study on Optimization of Multiparameter Combination for Horizontal Well Fracturing in Nonhomogeneous Conglomerate Reservoirs - Zehao Xu; Haiyang Zhao; Xiangjun Liu; Xiong Zhang; Pandeng Luo; Lixi Liang (Geofluids)
Optimizing multicluster fracturing designs in heterogeneous conglomerate reservoirs is critical due to their complex characteristics. This study employs the continuous–discontinuous element method (CDEM) to conduct engineering-scale 3D simulations using a mathematical model incorporating rock strength heterogeneity. A predictive model relating stimulated reservoir volume (SRV) to in situ stress, stage, cluster parameters, and well azimuth was developed, with SRV maximization as the objective. Results demonstrate that larger stage lengths combined with increased cluster counts enhance SRV as stress difference increases. However, a significant bottleneck in SRV growth occurs once the stress difference exceeds 20 MPa, rendering further stage/cluster adjustments ineffective. Crucially, the optimal stage/cluster combination depends strongly on well azimuth. For conglomerate reservoirs with high stress differences, strategically adjusting the well azimuth can increase fracture complexity, effectively overcoming the SRV bottleneck and enabling sustained high SRV even under elevated stress differences.